MODEL INKUIRI TERBIMBING DALAM PEMBELAJARAN KONSEP PENGHEMATAN AIR DI KELAS V SEKOLAH DASAR - Muhammad Zaini (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2014)
Abstract: Guided inquiry model in teaching water conservation concept in fifth grade of elementary school. Purpose of the research was to determine influence inquiry teaching on process learning achievement, measuring process skills, cooperation competency, students’ questioning competency. Type of research was descriptive and experimental. Results of the research were the guided inquiry teaching influenced on product learning achievement, the guided inquiry learning influenced on process learning achievement, students’ process skills when they involved in guided inquiry learning were categorized good, guided inquiry learning improved students; cooperation, and guided inquiry learning improved students’ questioning competency.Keywords: guided inquiry, water conservation, product, process, elementary school.Abstrak: Penelitian bertujuan menentukan pengaruh pembelajaran inkuiri terhadap hasil belajar proses, mengukur keterampilan proses, kemampuan kerjasama, dan kemampuan bertanya siswa. Jenis penelitian deskriptif dan eksperimental. Hasil penelitian menunjukkan: pembelajaran inkuiri terbimbing berpengaruh terhadap hasil belajar produk, pembelajaran model inkuiri terbimbing berpengaruh terhadap hasil belajar proses, keterampilan proses siswa selama pembelajaran inkuiri terbimbing tergolong baik, pembelajaran inkuiri terbimbing mampu meningkatkan kerjasama siswa, dan pembelajaran inkuiri terbimbing mampu meningkatkan kemampuan bertanya siswa.Kata Kunci: inkuiri terbimbing, penghematan air, produk, proses, SD